Effects of different PETTLEP imagery training methods on high school basketball players’ jump-shot performance, self-confidence and anxiety - Ting-Hong Chien; Jo-Yun Chen; Szu-Yu Chen; Li-Kang Chi (Asian Journal of Sport and Exercise Psychology, 2022)
Holmes and Collins (2001) proposed functional equivalence from a neuroscience perspective. They also argued that imagery execution and movement will bring out the same neuro mechanism that leads to benefits for sport performance. In this study, we aimed to apply different delivery intervention methods to investigate the effects of regular (RI), progressive (PI), and retrogressive (RETI) PETTLEP imagery patterns to jump-shot performance, state anxiety, and self-confidence of basketball players. Participants were recruited from 4 high-school basketball teams of Division II league. They were randomly assigned to a RI group, PI group, RETI group or a control group. Three intervention groups were implemented by following the 7 elements of the PETTLEP model. The intervention was delivered three times a week for 4-weeks, a total 12 imagery training sessions. The results showed: (1) PI and RETI significantly improved performance of running jump shooting, (2) RI and PI significantly reduced players’ state anxiety, (3) RI and PI significantly improved players’ self-confidence. To sum up, different imagery training patterns are beneficial to efficient learning for young athletes under certain circumstances that will improve sport performance, self-confidence, and reduce state anxiety levels. However, we recommend further exploration of the efficiency of different imagery intervention patterns among diverse age levels and sports. Lastly, in order to strengthen the effectiveness of imagery training, practitioners are suggested to provide different imagery patterns to match different skill development stages of athletes.